GROWTH PERFORMANCE AND TISSUE FATTY ACID COMPOSITION OF CYPRIUS CARPIO (LINN.) REARED ON FEEDS CONTAINING ANIMAL FATS AS FISH OIL REPLACEMENT - SONU BAWEJA,; BHUPINDER K. BABBAR, (The Bioscan, 2015)
A sixty day feeding experiment was conducted to study the effect of fish oil replacement in the diet of common carp fingerlings with two terrestrial animal fats viz. poultry fat (PF) and goat fat (GF) on survival, growth performance and fatty acid composition. Nine isonitrogenous and isoenergetic diets were formulated, containing 20% lipid sources. Fish oil (FO) was used in control diet, which was substituted by 25%, 50%, 75% and 100% with the alternative lipid sources in other eight diets. Survival rate recorded during the experimental period was 100% for all treatment groups. Net weight gain (1.22-1.41g), specific growth rate (0.19-0.22%) and proximate composition of fish fed different experimental diets were not significantly different (p ≤ 0.05). However, tissue fatty acid compositions differ significantly among fish fed control diet and other treatment diets). The n-3/n-6 ratio of fish fed control diet (diet 1) was quite higher (1.31%) compared to that in fish fed the other diets. In conclusion, the results show that partial replacement (25 to 50%) of fish oil with animal fats is possible without any negative effect on growth performance, survival, proximate and fatty acid composition of fish with an additional benefit of reduction in the cost of fish feed.